Risk factors for Depression and Coping Mechanisms among Physically Challenged Beggars in Nsukka Urban, Enugu State - Ofuebe , Justina; Iwuagwu, Tochi (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2017)
The study was conducted to examine risk factors for depression and coping mechanisms among physically challenged beggars in Nsukka Urban, Enugu State. The study adopted cross-sectional survey design. Four research questions and two null hypotheses guided the study. The study sample was 50 physically challenged beggars purposively selected from two Roman Catholic Churches, motor parks and within the University of Nigeria, Nsukka premises. The total population of beggars in Nsukka Urban was difficult to define because beggars often change their location from time to time. Questionnaire and in-depth interview guide were used as instruments for data collection. Percentages, means and standard deviations were used to answer the research questions while chi-square statistic was used to test the null hypotheses at .05 level of significance. Results of the study among others indicated that very high proportion of physically challenged beggars (71.7%) reported the common risk factors for depression such as poverty, traumatic or sad experiences, stigma and discrimination, genetic disposition, and chemical or hormonal imbalance. Depressive symptoms were reported by PCBs as indicated by a grand mean of 3.19. A moderate proportion of PCBs (54.3%) reported the common consequences of depression such as getting angry and crying, feeling weak and sickly sometimes, unable to work or do anything, drinking alcohol, feeling like dying, feeling uncomfortable, using abusive languages, and smoking cigarette. There were no significant differences in responses of PCBs on risk factors for depression based on gender and duration of begging. Findings also showed that beggars managed or cope with depression by using abusive words on offenders, playing, watching films, drinking, eating well when there is money, trekking if there is no money and talking with people. Based on the findings, recommendations were made among which is that the government should enact and implement laws of protection and provision that favour the physically challenged beggars, this will prevent or minimize to a large extent the risk factors and consequences of depression on physically challenged beggars